Inflation Accounting Effects on Financial Statement Interpretation Accuracy (gjstudies, 2016)
This research investigates the impact of inflation accounting methodologies on theaccuracy of financial statement interpretation by non-expert users, a critical yet underexplored area at the intersection of accounting, information systems, and cognitivescience. Traditional research has focused on compliance and valuation effects for professional analysts, neglecting how methodological choices in presenting inflation-adjusteddata influence the decision-making accuracy of managers, investors, and regulatorswithout specialized accounting training. We propose a novel, cross-disciplinary experimental methodology that integrates principles from information visualization, cognitive load theory, and behavioral finance. Participants were presented with identicalunderlying financial data from a simulated manufacturing firm over a ten-year periodof high inflation, but formatted using four different inflation accounting presentationframeworks: Current Purchasing Power (CPP), Current Cost Accounting (CCA) withphysical capital maintenance, a hybrid CPP-CCA narrative format, and a control groupusing historical cost accounting only. Accuracy of interpretation was measured througha series of tasks assessing profitability judgment, liquidity assessment, and long-termviability prediction, with response time and confidence levels recorded. Results demonstrate a significant and non-linear relationship between accounting methodology andinterpretation accuracy. Contrary to expectations that more complex adjustments(CCA) would reduce accuracy, we found the structured, asset-focused CCA presentation led to a 22% higher accuracy in long-term viability judgments compared tohistorical cost, though it reduced accuracy in short-term liquidity assessments by 15%.The hybrid narrative format, while increasing time-to-decision by 40%, produced themost balanced accuracy across all task types. A key novel finding is the identificationof a ’cognitive reconciliation gap’: users presented with CPP data, which adjusts allitems by a general price index, demonstrated high confidence but the lowest actualaccuracy, particularly in overestimating real profitability. This gap between confidenceand competence presents a significant risk for decision-making. The study concludesthat the design of inflation accounting information systems is not a neutral reporting exercise but a fundamental determinant of decision quality. We contribute a newframework for ’cognitive-aware accounting presentation’ that prioritizes the interpretative outcomes for end-users, arguing that accounting standards must consider notjust the computational correctness of inflation methods, but their cognitive effects onthe accuracy of financial statement interpretation.